Supply of Bamboos to the Nepa Mills, Nepanagar - Tomar, M. S. (Indian Forester, 1960)
Bamboo bearing areas of the teak forests of Bori range of Hoshangabad division (Madhya Pradesh) form an important source of supply of bamboos to the Nepa Mills. Economics and methods of bamboo exploitation are discussed. The relevant data was collected in 1957.